PENGARUH PELAYANAN PAJAK, PERSEPSI SISTEM PERPAJAKAN, PENGETAHUAN PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - ., Waluyo (STIE Binaniaga, 2012)
This research aims to analyze the impact of tax apparatus service, perception of effective tax system, knowledge of tax, and awareness of individual taxpayers on tax compliance, as well as to obtain empirical evidence on research conducted either empirically or simultaneously. The research method used is a causal study. Causal study means that the researchers wanted to examine the relationship between independent variables with dependent variable.The populations of research was all individual taxpayers registered in the tax office (KPP). The sample of population used is an individual taxpayer who enrolled in tax office Tigaraksa especially around in Kelapa Dua subdistrict at period 2012. Sample was used 102 respondence. These results indicate that variable tax apparatus service have effect on individual taxpayer compliance, variable perception of effective tax system didn’t have effect on individual taxpayer compliance, knowledge of tax have effect on individual taxpayer compliance, and awareness of individual taxpayers have effect on individual taxpayer compliance. Variable tax apparatus service, perception of effective tax system, knowledge of tax, and awareness of individual taxpayers have simultaneously on tax compliance.Keywords: tax service, perception of effective tax system, knowledge of tax, awareness of individual tax payers and tax compliance.